Differences in Creative Thinking Abilities and Learning Interest Using the Mnemonic Learning Model - Ida Ermiana; Asri Fauzi; Lalu Hamdian Affandi; Nur Hasanah; Aisa Nikmah Rahmatih; Sutrisna Jumhari (MIMBAR PGSD Undiksha, 2025)
Low levels of creative thinking skills and learning interest often hinder students in understanding and retaining learning concepts. Learning should not merely focus on memorizing information but also stimulate students’ imagination to generate new and meaningful ideas. This study aims to examine the effect of the mnemonic learning model on elementary students’ creative thinking skills and learning interest compared to direct instruction. The research employed a quasi-experimental method with a non-equivalent control group design. The population consisted of 84 students, and 56 students were selected as the sample, divided into experimental and control groups. Research instruments included a creative thinking skills test and a learning interest questionnaire. Data analysis was initiated with assumption testing, including normality, homogeneity of variance, and Box’s M test, followed by MANOVA and ANOVA. The results showed that all assumptions were fulfilled, indicating that multivariate analysis was appropriate to conduct. The MANOVA test revealed a significant simultaneous difference between the experimental and control groups on both variables. Furthermore, the ANOVA results indicated a significant effect of the mnemonic model on both creative thinking skills and learning interest. Therefore, the mnemonic learning model is proven effective in enhancing students’ creative thinking skills and learning interest in elementary education. The findings imply the importance of implementing mnemonic-based learning across various subjects to support more engaging, enjoyable, and creativity-oriented learning experiences for students.